Oliver Twist - Dickens, Charles, 1812-1870 ([Boston, Mass] : Thomson Heinle, 2007)
An orphan, reared in a workhouse, runs away to London where he is captured by a gang of thieves. The leering Artful Dodger, the murderous Bill Sikes and the master thief Fagin are just some of the unforgettable charavters in this heart-rendering tale
Title from container
Keywords: Orphans -- Fiction; Poor -- Fiction; Thieves -- Fiction; Kidnapping victims; London (England) -- Fiction